RESEARCH OF ESSENCE, TYPES AND LEVELS OF REALIZATION OF ORGANIZATIONAL AND ADMINISTRATIVE INNOVATIONS - Tamara G. Bondar (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the characteristics of the organizational and managerial innovations, the author proposed a classification of type sand levels of organizational and managerial innovations, disclosed their nature, specificity, levels of implementation.